Molecular diagnosis of the myeloproliferative neoplasms: UK guidelines for the detection of JAK2 V617F and other relevant mutations. (11th October 2012) - Bench, Anthony J.; White, Helen E.; Foroni, Letizia; Godfrey, Anna L.; Gerrard, Gareth; Akiki, Susanna; Awan, Abida; Carter, Ian; Goday‐Fernandez, Andrea; Langabeer, Stephen E.; Clench, Tim; Clark, Jordan; et al.
Summary Molecular genetic assays for the detection of the JAK2 V617F (c.1849G>T) and other pathogenetic mutations within JAK2 exon 12 and MPL exon 10 are part of the routine diagnostic workup for patients presenting with erythrocytosis, thrombocytosis or otherwise suspected to have a myeloproliferative neoplasm. A wide choice of techniques are available for the detection of these mutations, leading to potential difficulties for clinical laboratories in deciding upon the most appropriate assay, which can lead to problems with inter‐laboratory standardization. Here, we discuss the most important issues for a clinical diagnostic laboratory in choosing a technique, particularly for detection of the JAK2 V617F mutation at diagnosis. The JAK2 V617F detection assay should be both specific and sensitive enough to detect a mutant allele burden as low as 1–3%. Indeed, the use of sensitive assays increases the detection rate of the JAK2 V617F mutation within myeloproliferative neoplasms. Given their diagnostic relevance, it is also beneficial and relatively straightforward to screen JAK2 V617F negative patients for JAK2 exon 12 mutations (in the case of erythrocytosis) or MPL exon 10 mutations (thrombocytosis or myelofibrosis) using appropriate assays. Molecular results should be considered in the context of clinical findings and other haematological or laboratory results.